CO2 Storage in Deep Oceanic Sediments in the form of Hydrates: Energy Evaluation and Advantages Related to the Use of N2-Containing Mixtures - Alessia Di Giuseppe; Alberto Maria Gambelli (Energies, 2024)
Permanent storage in suitable geological sites and/or deep aquifers is emerging as the most concrete and effective solution to mitigate its increasing concentration in the atmosphere. This article experimentally investigated its storage in deep marine environments in the form of hydrates. Gas hydrates were formed into a small-scale reactor, designed to reproduce marine seafloors. Hydrates were formed with pure carbon dioxide and with CO2-based gaseous mixture containing nitrogen at different concentrations, equal, respectively, to 30, 50 and 60 vol%. The results obtained for each mixture were then compared to each other. In particular, the quantity of hydrates formed was evaluated as a function of the thermodynamic conditions selected for the experiments. The energy spent for the process, calculated by considering the cooling and compression phases, was calculated for the unit quantity of hydrates formed and for the unit quantity of carbon dioxide stored. Finally, the energy requirements for gas cooling and for gas compression were calculated separately in order to comprehend the contribution of the single process for each mixture.